From visual aerial photo interpretation and field soil survey to automated decoding and soil mapping by satellite imagery - M. S. Simakova (Бюллетень Почвенного института им. В.В. Докучаева, 2014)
Under consideration are the ways for the development and improvement of methods to compile soil maps in Russia as based upon the information on landforms and the earth surface obtained by different aerial and outer space devices. The ever increasing development of aviation, cosmonautics and modification of electronic engineering resulted in great changes taken place in the soil studies, thus affecting the quality and readability of soil maps. The ways for obtaining and decoding of the satellite imagery are described. The methods to study different characteristics of soil properties are considered as well. The automated methods of soil identification and mapping are realized now through the materials of remote sounding of the Earth’s surface.